Treatment with radiotherapy in carotidal paraganglioma: experience of the General Hospital of Mexico - Yicel Bautista Hernandez; Valeria Vazquez Herrera; Karina Vazquez Gomez; Ana Laura Lopez Martinez (Reports of Practical Oncology and Radiotherapy)
BACKGROUND: Paragangliomas are highly vascularized tumours that have benign histology, with malignant dissemination being infrequent (< 5%). Surgery is the only option offering complete resection; however, there is significant morbidity. Treatment with radiotherapy (RT) offers good results in controlling the disease. MATERIALS AND METHODS: Retrospective, observational and descriptive study from the RT Service of the General Hospital of Mexico conducted from January 1, 2016 to January 1, 2021 that included patients with carotid paraganglioma in whom RT response was evaluated by determining clinical and image size at the beginning of the study and end of follow-up. Correlation of response to treatment, and toxicity related to RT, were analysed. RESULTS: 55 patients were included, 92.7% were female, the mean age was 58.7 years, and the mean follow-up time was 28.87 months. The mean initial clinical size was 4.75 cm. Initial imaging study mean size was 4.76 cm. A total of 92.7% received intensity-modulated radiotherapy (IMRT) and conformal RT (7.3%), mean prescribed dose was 51.90 Gy (50–54), with a median of 50.4 Gy/25 fractions. The mean final clinical size was 3 cm. The final imaging study mean size was 3.48 cm. At the end of the study, 96.4% showed a response to treatment and 3.6% progressed. Analysis showed no significance between treatment response and RT dose (p < 0.5) or between RT response and the % dose to the planned treatment volume (PTV) (p = 0.91). Acute toxicity was found in 55 patients, with grade 1 radiodermatitis, and chronic toxicity in 44 patients, with atrophy grade 1. CONCLUSION: RT represents a therapeutic option in the management of patients with carotid paraganglioma because it offers a high probability of local control, without toxicity.